2020
DOI: 10.11118/actaun202068010129
|View full text |Cite
|
Sign up to set email alerts
|

Oilseed Rape (Brassica Napus L.) Nutrition by Nitrogen and Phosphorus and its Effect on Yield of Seed, Oil and Higher Fatty Acids Content

Abstract: The effect of phosphorus (P) and nitrogen (N) application on yield, oil and fatty acids content (especially oleic acid, linoleic acid and linolenic acid) in rapeseed was investigated in the field experiment. Also effect of weather conditions was evaluated. The polyfactorial trial was realized in experimental years 2013/2014 and 2014/2015 in terms of agricultural cooperative in Mojmírovce. The experiment was based on three variants of fertilization treatments by the block method in three replications. The size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Canola (or rapeseed or oilseed rape) belongs to Brassicaceae family. It is the most cultivated oil crop worldwide and there has been growing interest on it during the last two decades [105]. The main producing countries are Canada and China, which together account for the 38% of global production [73].…”
Section: Canola Main Featuresmentioning
confidence: 99%
“…Canola (or rapeseed or oilseed rape) belongs to Brassicaceae family. It is the most cultivated oil crop worldwide and there has been growing interest on it during the last two decades [105]. The main producing countries are Canada and China, which together account for the 38% of global production [73].…”
Section: Canola Main Featuresmentioning
confidence: 99%
“…Research conducted previously on mustard (Brassica juncea L.) showed that the highest phosphorus doses, namely 60 kg ha −1 (Mir et al, 2010;Singh & enua, 2016) and 50 kg ha −1 , resulted in the highest seed yield, oil content, and yield (Solanki et al, 2015). e highest dose of P application is extremely important for mustard cultivation and yield (Brennan & Bolland, 2009;Khan et al, 2000;Vicianová et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…One of these factors is plant nutrition. A well-designed fertilizer system in compliance with all the norms and terms of organic and mineral fertilizer application will provide a significant increase in the yields of winter rapeseed that will not require extra land [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%